Gustav Landauer : le devenir révolutionnaire comme alternative anarchiste - Anatole Lucet (Recherches Germaniques)
German philosopher and activist Gustav Landauer (1870-1919) promoted an original form of “anarchism-socialism”, thereby challenging social and political standards under Wilhelm II. In questioning the norms of his time and their crystallization into a lasting system, Landauer advocated a return to the individual in order to build a community. His project of a society to be build “through separation” is an invitation for individuals to severe the artificial ties to existing institutions in order to find in the spirit that inhabits every living being the root of their longing for community. His conception, which is as much based on experiments made by “life reformers” as it was an inspiration for them, relies on the action of creative individuals in charge of their destiny. In the shadow of the mainstream political systems of his time, Landauer’s work is full of concrete propositions for the implementing alternatives. It also offers a reflection on alternativeness itself.